The Relationship between Self-Efficacy and Career Maturity in Class X Students of SMA Negeri 11 Makassar - Nurdin, Nur Afika; Alwi, Ahkam (Polteknik Ilmu Pemasyarakatan, 2024)
Students are individuals who study at an educational institution to gain knowledge and understanding in various fields. One of the developmental tasks that must be fulfilled by high school (SMA) students is to reach maturity in choosing a career that will then be developed. This research aims to determine the relationship between self-efficacy and career maturity in class X students at SMA Negeri 11 Makassar. A total of 184 people were determined using the cluster random sampling technique as respondents. The self-efficacy and career maturity scales are the measuring tools used in this research. The data analysis used in this research is pearson product moment correlation which was processed using SPSS 25 for Windows. The results of this study show that there is a positive and significant relationship between self-efficacy and career maturity in class X students at SMA Negeri 11 Makassar (r = 0.389, p = 0.001 < 0.05). This research can be a foundation for students in achieving their academic and professional goals, a strong belief in their own abilities makes students feel moreable to face challenges, and understand career options that align with their personal interests and values.